Electrochemical characterisation of carbon paste electrodes modified with different surfactants - Sýs, Milan; Mikysek, Tomáš (Univerzita Pardubice, 2019)
This electrochemical study is focused on the carbon paste electrodes modified with deliberately selected surfactants, namely TritonTM X-100, sodium dodecyl sulfate (SDS) and didodecyldimethylammonium bromide (DDAB). Comparison of the electrochemical properties of these composite sensors towards 3,5-di-tert-butylbenzo-1,2-quinone/3,5-di-tertbutylbenzene-1,2-diol redox couple is presented. From these surfactants, SDS seems to be the most suitable CPE modifier. In addition, it has been found that the content of this surfactant significantly affects the reversibility of electrode reaction. It can be concluded that only CPEs modified with SDS could be used for upcoming electroanalytical purposes.
Elektrochemická charakterizace uhlíkových pastových elektrod modifikovaných různými povrchově aktivními látkami
Keywords: Carbon paste electrode; modification; surfactant; cyclic voltammetry; Uhlíková pastová elektroda; modifikace; povrchově aktivní látka; cyklická voltametrie